Mixed‐methods evaluation of a continuing education approach to improving district hospital care for children in Lao PDR. Issue 3 (13th February 2022) - Safe, Marianne; Wittick, Penelope; Philaketh, Khammanh; Manivong, Amphayvanh; Gray, Amy
Abstract: Objective: To understand the impact of a multifaceted intervention on improving acute hospital care provided to children in two district hospitals in northern Lao PDR. Methods: We developed a continuing education intervention, which integrated separate program content using a common pool of facilitators and low‐fidelity simulation scenarios. Coaching was delivered over one year through two‐day hospital visits to each hospital six to eight weeks apart with visits incorporating feedback. A comparative case study was conducted between two hospital sites. Medical record abstraction from inpatient cases was performed at each visit. Focus groups and interviews with staff were conducted to understand perceived changes to case management. Results: Inpatient case management scores showed incremental improvement over time, from 50% at baseline to 80% at the end of one year at Hospital A and 52% to 97% at Hospital B. The key themes that emerged from the qualitative data from both hospitals were the value of the educational method and increased belief in capability. Hospital B showed more incremental and sustained improvement. Qualitative data revealed that the directors of Hospital B demonstrated modelling and behavioural reinforcement. Conclusion: Improving the quality of care in low‐resource settings is feasible. A hands‐on practical approach with repeated coaching visits reinforced by feedback can lead to behaviour change. Optimal impact requires harnessing leadership and motivation for change among health workers.